Specificities and problems of montenegrin transition - Veselin Drašković (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
Montenegrin transition has acquired in some of its significant aspects an opposite developmental approach of a destructive and deeply in crisis character. Economically inefficient socialist system transformed into a conglomerate like unsystemic structure, mutantly recombined order, which contains many anachronous structures of the old system and surpassed rigid elements of capitalist system. The subject of this paper is diagnosis and critical analysis of braking factors of Montenegrin transition generated in discrepancy between propagated mass-society character of the country and realized privileged individuality. The goal of the article is to point out at urgent need to a) build an efficient institutional structure, which represents a precondition for overcoming consequences of transitional crisis, namely, the substitution of institutional adaptations, imitations and improvisations with institutional innovations, and b) adapt to successful role models of foreign countries and to adopt achievements of the civilization.
Keywords: 330; Transition; Institutionalization; Economic Institutions; Quasiinstitutionalization; Privatization; Efficient Owner; Systemtransformation; Wirtschaftsreform; Institutioneller Wandel; Montenegro